Late diagnosis of mitral valve myxomatous degeneration and obesity and tachycardia as prognostic complicating cofactors - Case report (Research, Society and Development, 2023)
Myxomatous mitral valve degeneration is among the most common heart diseases in dogs, causing changes in the heart valves that degenerate and progress to atrial ventricular overload. This disease can be treated according to the stage of the disease, ranging from A to D, with subdivisions in stage B to B1 and B2. In this case report we present the late diagnosis of an elderly female dog in stage C, and obesity and tachycardia as complicating cofactors of the disease, will be addressed. Obesity is characterized by the accumulation of adipose tissue, it is associated with genetic and hormonal factors and metabolic disorders that can generate cardiac dysfunction, however, the heart dilates, requires greater effort, increases the heart rate and it becomes impracticable to maintain this HR for a prolonged period. An 8 years-old Shih Tzu female dog, weighing 10,3 Kg, was seen in private practice in a city in the state of Goiás. On clinical examination, she was dyspneic and apathetic, RR 48 mrm, HR 240 bpm, on cardiac auscultation she had a grave V murmur. The echocardiogram showed advanced myxomatous mitral valve degeneration and pulmonary edema. Therapy with furosemide, pimobendan, atenolol, amlodipine and benazepreil, was started, but the patient died. This report aims to show the importance of early diagnosis of the disease and obesity and tachycardia as complicating prognostic cofactors. The dog had a quick diagnosis, but without a timely and desirable drug effect. The necropsy was not authorized for further studies.